PREVALENCE OF CHRONIC KIDNEY DISEASE AMONG COMMUNITY REMOTE AREAS IN SABAH: POPULATION-BASED STUDY - Nor Ain Mior Nizam; Malehah Mohd Noh; Shamsul Bahari Shamsuddin (UNUSA Press, 2020)
In this population-based study, we determined the prevalence of chronic kidney disease of community in remote areas of Ranau, Sabah to have accurate information for health-care planning. It also investigated the association of risk factors with the prevalence of CKD. A sample of 270 individuals, compared to the study of the National Health and Morbidity Survey 2011, of the adult population (over 18 years old) undertaken in West Malaysia. We measured the estimated glomerular filtration rate (eGFR) using this CKD-EPI equation. The total prevalence of chronic kidney disease in this group was 53%. An estimated 3.3% had stage 1 chronic kidney disease (eGFR >90 ml/min per 1.73m2), 32.6% had stage 2 (eGFR 60–89 ml/min per 1.73m2), 4.1% had stage 3 (eGFR 30–59 ml/min per 1.73m2), 7% had stage 4 (eGFR 15–29 ml/min per 1.73m2), and 6% had stage 5 chronic kidney disease (eGFR <15 ml/min per 1.73m2). Only 4% of respondents with chronic kidney disease were aware of their diagnosis. The significant risk factors included family history of kidney disease, alcohol consumption, smoking status, hypertension, diabetes mellitus, and dyslipidemia. Thus, chronic kidney disease in East Malaysia is common and warrants early detection, and treatment to potentially improve outcomes can be implemented.